RESEARCH ON PROPAGATION TECHNIQUES OF Arundinaria sp. BY RHIZOME CUTTING - Van Dien, Nguyen; Xuan Truong, Le; Hong Lien, Le; Ngoc Hieu, Vu; A Phong, Giang (Journal of Forestry Science and Technology, 2021)
Arundinaria sp. is a valuable non-timber forest product, capable of improving the economic life of local people based on export demand to countries such as Japan, Taiwan, and Europe. The need for materials in the area for processing Arundinaria sp. culm to export is quite high in recent year. Therefore, develop Arundinaria sp. plantation becomes a key solution to supply sustainable raw material for Arundinaria sp. culm processing and producing seedling is the first and an important method that need to be well prepared. Arundinaria sp. rhizome was treated with IBA growth regulator agent at a concentration of 200 ppm for the best rooting rate and root quality. Age of cuttings at age 1 gave the best results in terms of rooting rate, while at age 2 with the best root quality. Container that has mixture of top soil + NPK fertilizer with IBA 200 ppm gave better rooting rate and root quality than that of clean sand. Treatment of Arundinaria sp. cuttings on 95% top soil + 5% NPK fertilizer with 200 ppm IBA gave the best rooting rate and root quality compared to the other experimental treatments. The technique of propagating Arundinaria sp. by cutting from rhizome is a good method, it is necessary to apply and conduct propagation from rhizome cuttings to serve the future afforestation work.